TT

Rut gon bieu thuc

(x+1)2 - (x-1)- 3. (x+1). (x-1)

TT
30 tháng 6 2016 lúc 8:17

\(=\left(\left(x+1\right)^2-\left(x-1\right)^2\right)-3\left(x^2-1\right)\)

\(=4x-3x^2+1\)

Bình luận (0)
TT
30 tháng 6 2016 lúc 8:18

nhầm

\(=4x-3x^2+3\) nhé

Bình luận (0)
DK
30 tháng 6 2016 lúc 8:21

\(\left(x+1\right)^2-\left(x-1\right)^2-3.\left(x+1\right)\left(x-1\right)\)

\(=\left(x+1+x-1\right).\left(x+1-x+1\right)-3.\left(x^2-1\right)\)

\(=2x.2-3x^2+3=4x-3x^2+3\)

Bình luận (0)
DN
30 tháng 6 2016 lúc 8:24

= (x+1+x-1)(x+1-x+1) - 3(x2 -1)=

=4x - 3x2 +3

Bình luận (0)